Support of Mental Health And Psychosocial on Body Resistance In Comorbid Patients In The Time of Covid-19 - Adi, Wien Soelistyo; Ramelan, Ramelan; Wijayanti, Sugih; Windiarti, Sri Endang (Syntax Literate, 2021)
People infected with COVID 19 if there are comorbidities in the patient's body can increase the risk status of these patients, such as hypertension, diabetes, and other diseases. Other lung conditions, such as tuberculosis, pneumonia and others. These diseases are often called comorbid diseases. Patients who are positively infected with Covid-19 can have severe and incriminating symptoms if they have these comorbidities or comorbidities. This study aims to increase the patient's psychological resilience to reduce more severe symptoms and speed up recovery. This research will be conducted with a quasi-experimental design with pretest and posttest designs, conducted in the Banyumanik sub-district in patients with comorbid COVID-19. Comorbid Covid 19 patients in sub- Banyumanik District. Ethical Clearance. The results of the T-test analysis of the effect of mental health support on body resistance before and after the action on comorbid patients during the COVID-19 pandemic showed a significant difference between before and after treatment with a p-value of 0.018, meaning that health support had a significant effect. The application of mental health support is proven to affect body resistance with operational standards of mental health support which include physical relaxation, positive emotions, positive behaviour, positive relationships, positive spirituality. Future research is expected to support mental health effects on body resistance physiologically so that there are better-known benefits